Students’ and Teachers’ Perceptions of Metaphor-Based Visual Media in Cell Biology Learning - Jayaman Wibowo; Anna Fitri Hindriana; Zaenal Abidin (Quagga: Jurnal Pendidikan dan Biologi, 2025)
This study aims to develop an innovative instructional medium designed in the form of a visual metaphor-based learning media, specifically for the topic of cells in the science subject (IPA) at the junior high school level Class VIII in SMP Negeri 1 Plumbon. The topic of cell structure and function is often perceived as abstract and difficult for students to understand due to its microscopic nature and the spatial imagination it requires. This study employs a descriptive quantitative method by collecting and analyzing data in the form of student and teacher responses to the use of the media. The primary instrument used was a questionnaire designed to assess student and teacher perceptions regarding the effectiveness, appeal, ease of use, and usefulness of the media in supporting the learning process. The questionnaire was distributed after the classroom implementation of the visual metaphor-based learning media. The analysis results showed that the average student response score reached 89.25%, which falls into the "very positive" category. This indicates that the majority of students felt aided in understanding difficult concepts through metaphorical visualization, which was able to simplify complex biological information. In addition, teacher responses also indicated enthusiasm and support for the use of this media, as it was considered capable of increasing student engagement, deepening conceptual understanding, and encouraging reflective thinking. Therefore, the application of visual metaphor-based media holds great potential to support a more humanistic, contextual, and meaningful transformation of the learning process.